Cerebral Expression of Glial Fibrillary Acidic Protein, Ubiquitin Carboxy-Terminal Hydrolase-L1, and Matrix Metalloproteinase 9 After Traumatic Brain Injury and Secondary Brain Insults in Rats. Issue 14 (May 2019) - Mrozek, Ségolène; Delamarre, Louis; Capilla, Florence; Al-Saati, Talal; Fourcade, Olivier; Constantin, Jean-Michel; Geeraerts, Thomas
Glial fibrillary acidic protein (GFAP), ubiquitin carboxy-terminal hydrolase-L1 (UCH-L1), and matrix metalloproteinase 9 (MMP-9) are potential biomarkers of traumatic brain injury (TBI) but also of secondary insults to the brain. The aim of this study was to describe the cerebral distribution of GFAP, UCH-L1, and MMP-9 in a rat model of diffuse TBI associated with standardized hypoxia-hypotension (HH). Adult male Sprague-Dawley rats were allocated to Sham (n = 10), TBI (n = 10), HH (n = 10), and TBI+HH (n = 10) groups. After 4 hours, brains were rapidly removed and immunostaining of GFAP, UCH-L1, and MMP-9 was performed. Areas of interest that have been described as particularly sensitive to hypoxic insults were analyzed. For GFAP, in the neocortex, immunostaining revealed a significant decrease in strong staining for HH and TBI+HH groups compared with TBI group ( P  < .0001). For UCH-L1, the total immunostaining (6 regions of interest) reported a significant increase in strong staining ( P  < .0001) and decrease in weak staining ( P  < .0001) for the HH and TBI+HH groups compared with the Sham and TBI groups. For MMP-9, for the HH and TBI+HH groups, a significant increase in moderate ( P  < .0001) and weak staining ( P  < .0001) and a decrease in negative staining ( P  < .0001) compared with the Sham and TBI groups were observed. UCH-L1 and MMP-9 immunostainings increased after HH alone or HH combined with TBI compared with TBI alone. GFAP immunostaining decreased particularly in the neocortex after HH alone or HH combined with TBI compared with TBI alone. These three biomarkers could therefore be considered as potential biomarkers of HH insults independently of TBI.